New Media and Religious Transformations in Africa - Soares, Benjamin F.; Hackett, Rosalind I. J. (Book collections on Project MUSE., 2015)
New Media and Religious Transformations in Africa casts a critical look at Africa's rapidly evolving religious media scene. Following political liberalization, media deregulation, and the proliferation of new media technologies, many African religious leaders and activists have appropriated such media to strengthen and expand their communities and gain public recognition. Media have also been used to marginalize and restrict the activities of other groups, which has sometimes led to tension, conflict, and even violence. Showing how media are rarely neutral vehicles of expression, the contribut.